2017
DOI: 10.4081/ijfs.2017.6879
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing for typing and characterisation of Listeria monocytogenes isolated in a rabbit meat processing plant

Abstract: Listeria monocytogenes is a food-borne pathogen able to survive and grow in different environments including food processing plants where it can persist for month or years. In the present study the discriminatory power of Whole Genome Sequencing (WGS)-based analysis (cgMLST) was compared to that of molecular typing methods on 34 L. monocytogenes isolates collected over one year in the same rabbit meat processing plant and belonging to three genotypes (ST14, ST121, ST224). Each genotype included isolates indist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Interestingly, six (100%) ST9/CC9 and one (25%) ST5/CC5 isolates harbored PMSCs in the inlA gene, concurrent with previous studies reported in China (Chen et al, 2018a(Chen et al, , 2019a. Similarly, the PMSCs in the inlA gene were frequent in ST121/CC121 strains, which were predominant in foods and associated environments (Ciolacu et al, 2015;Palma et al, 2017;Rychli et al, 2017Rychli et al, , 2018. These data indicate that the ST9 and ST121 strains predominant in foods may acquire PMSCs in the inlA gene.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, six (100%) ST9/CC9 and one (25%) ST5/CC5 isolates harbored PMSCs in the inlA gene, concurrent with previous studies reported in China (Chen et al, 2018a(Chen et al, , 2019a. Similarly, the PMSCs in the inlA gene were frequent in ST121/CC121 strains, which were predominant in foods and associated environments (Ciolacu et al, 2015;Palma et al, 2017;Rychli et al, 2017Rychli et al, , 2018. These data indicate that the ST9 and ST121 strains predominant in foods may acquire PMSCs in the inlA gene.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, three fourths of isolates with PMSCs belonged to ST9 in this study. In contrast, none of the ST121 isolates was identified as PMSC, which was most identified as PMSCs in food and associated environments in the other countries ( Hein et al, 2011 ; Ciolacu et al, 2015 ; Palma et al, 2017 ). In recent years, LIPI-3 genes were identified as important virulence factors that acts to target the host gut microbiota, responsible for the majority of listeriosis outbreaks ( Cotter et al, 2008 ; Quereda et al, 2017 ), and human central nervous system (CNS) or MN listeriosis was mainly attributed to LIPI-4 ( Maury et al, 2016 ).…”
Section: Discussionmentioning
confidence: 90%
“…In the last decades, several studies aiming to determine the basis of persistence in RTE industry and to trace-back outbreaks-related L. monocytogenes strains have been performed based on conventional molecular typing [72][73][74][75]. However, the advantages provided by analyses of genome-scale data through comparative genomic approaches have been recently demonstrated in the context of L. monocytogenes strains persisting in FPEs [4,16,18,19,23,[76][77][78]. These studies also suggested differences in distribution and fitness of CCs in geographical regions and evolutionary niches.…”
Section: Discussionmentioning
confidence: 99%